Recent Developments in Bombay Forests - Kaikini, N. S.; Bhathena, B. S. (Indian Forester, 1955)
The most important problems encountered in the practice of Forestry in Bombay State are represented and the manner in which they are overcome is elucidated with a brief description of the forests forming a suitable background. Some achievements of silvicultural research and investigations on the best utilization of forest produce have been brought out and the direction in which further progress is anticipated is indicated.